Chaînes opératoires and resource-exploitation strategies in chimpanzee (Pan troglodytes) nut cracking - Carvalho, Susana (2008)
We apply archaeological methods to extend our knowledge of chimpanzee material culture. The chaîne opératoire conceptual framework, as introduced by ethnography, established technology as a phased process. Prehistoric archaeology adopted this concept to elucidate technological variability in tool-making procedures, based on knowledge of tool functions or subsistence patterns. We focused on the detection of operational sequences by wild chimpanzees (Pan troglodytes verus) when nut cracking with lithic implements at the sites of Bossou and Diecké, Guinea, West Africa. Thus, while it has recently been claimed that chimpanzees leave behind recognizable assemblages of stone hammers that can be morphologically distinguished from Oldowan hammers, this is the first study to focus specifically on the existence of operational sequences during the utilization of stone tools by wild chimpanzees. By combining primatological and archaeological methods and examining ecological areas inhabited by different chimpanzee groups, we sought technological variability and identified variables influencing regional diversity in tool typology and technology. We compared three case studies: (1) Bossou--direct recording of experimental nut-cracking sessions; (2) Bossou-- direct and indirect monitoring of nut-cracking sites in the wild; (3) Diecké--indirect monitoring of nut-cracking sites in the wild. Results suggest that chimpanzees perform sequences of repeated tool transport and nut cracking. Data show discrimination of tool functions based on tool features. We identified the most technologically complex tool for nut cracking, which was composed of four stones. We found regional diversity in chimpanzee stone assemblages. Raw-material type and tool mobility constrain technological development in human and nonhuman primates. Spatial analysis of tool distribution indicates a pattern of resource-exploitation strategy, revealing affinities with Oldowan.